Voir une chenille, dessiner un serpent à plumes. Une relecture analogique de l’hybridité et des êtres imaginaires en Mésoamérique préhispanique - Dimitri Karadimas (Journal de la Société des Américanistes)
This contribution suggests to look at the figure of Quetzalcoatl – in the Teotihuacan iconography as in the later Aztec one – by analyzing imaginary beings and the representations of hybrids in Mesoamerica as an analogical transcription of real beings according to the principles of formal analogy. After going through a review of the perception processes entering in the way the names of species are built in natural languages, we apply these processes to iconographical materials that combines distinct beings – or parts of beings –, this enables us to interpret their occurrences on feather headdresses or as mythological figures.